Macrophage-modulating cytokines predict adverse outcome in heart failure - Hohensinner, Philipp J.; Rychli, Kathrin; Zorn, Gerlinde; Hülsmann, Martin; Berger, Rudolf; Mörtl, Deddo; Richter, Bernhard; Huber, Kurt; Wojta, Johann; Pacher, Richard; Niessner, Alexander (Thrombosis and Haemostasis, 2010)
Cytokines regulating the mobilisation, recruitment and survival of mononuclear cells may play an important role in progression of heart failure. Therefore, we investigated the role of granulocyte colony stimulating factor (G-CSF), monocyte chemoattractant protein 1 (MCP-1) and macrophage colony stimulating factor (M-CSF) in patients with advanced heart failure. G-CSF, MCP-1 and M-CSF were determined in plasma of 351 patients with advanced heart failure by specific ELISAs. During a median follow up period of 16 months (95% confidence interval [CI]: 15–17 months) 175 patients (50%) experienced the composite endpoint rehospitalisation and all-cause mortality. M-CSF tertiles were associated with a gradually increasing risk with hazard ratios (HR) of 2.2 (95% CI: 1.5–3.2; for trend, p<0.001) for the composite endpoint and 2.6 (95% CI: 1.5–4.6; for trend, p=0.002) for all-cause mortality comparing third and first tertile. These associations remained significant in a multivariable Cox regression model after adjustment for BNP and other known risk factors (p=0.043 and p=0.024). High MCP-1 concentrations were associated with an increased risk of all-cause mortality with an adjusted HR of 1.9 (third vs. first tertile, 95% CI: 1.1–3.3; for trend, p=0.034). In contrast, G-CSF tertiles were not significantly associated with the composite endpoint or all-cause mortality in multivariable Cox regression. In conclusion, the independent and concentration-dependent association of macrophage-modulating cytokines and in particular of M-CSF with adverse outcome in advanced HF patients suggests that these cytokines may play an important pathophysiological role in progression of cardiomyopathy.
Keywords: Heart failure; cardiomyopathy; cytokines; macrophages